2020
DOI: 10.3390/molecules25163729
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic of Polyphenols Concentrations in Organic and Conventional Sour Cherry Fruits: Results of a 4-Year Field Study

Abstract: Sour cherry fruits are a perfect source of polyphenols, including flavonols, phenolic acids and anthocyanins. According to the literature, organic fruits contain more bioactive compounds, especially polyphenols, compared to conventional fruits. Given that only one two-year experiment on the status of polyphenols in sour cherry fruits in an organic farm was previously conducted and found in the existing scientific literature, the aim of this study was to analyse and compare the concentration of bioactive compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The remaining flavonoids (quercetin and its derivatives, and myricetin) were abundant at higher concentrations in organic pansy flowers ( Table 2 a). Similar relationships were presented for organic and conventional sour cherries and raspberries [ 39 , 66 ]. Pansy flowers with violet/yellow pigmentation were characterized by higher concentrations of quercetin-3- O -rutinoside, quercetin-3- O -glucoside, and pure quercetin than yellow pansy flowers.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The remaining flavonoids (quercetin and its derivatives, and myricetin) were abundant at higher concentrations in organic pansy flowers ( Table 2 a). Similar relationships were presented for organic and conventional sour cherries and raspberries [ 39 , 66 ]. Pansy flowers with violet/yellow pigmentation were characterized by higher concentrations of quercetin-3- O -rutinoside, quercetin-3- O -glucoside, and pure quercetin than yellow pansy flowers.…”
Section: Resultssupporting
confidence: 58%
“…There were no similar results, so the concentration of flavonoids in pansy flowers was compared with that of strawberry and sour cherry fruits. As reported in the literature, organic fruits are characterized by a higher concentration of flavonoids than conventional fruits [ 65 , 66 ]. The authors have much more information on the differences in the contents of flavonoid compounds in pansy flowers with different petal pigmentations.…”
Section: Resultsmentioning
confidence: 99%
“…In studies carried out on other fruits belonging to the Prunus genus, the obtained levels of phenolic acids were much lower than those obtained in this study, which leads us to consider that Prunus lusitanica fruits are a valuable source of hydroxycinnamic acids. Głowacka et al [ 63 ] carried out a 4-year study on sour cherry ( Prunus cerasus ) and obtained maximum concentrations of 7.6 mg/100 g fw of phenolic acids. In Prunus avium , Mikulic-Petkovsek et al [ 19 ] found a total hydroxycinnamic acid value of 44.24 mg/100 g fw, and Średnicka-Tober et al [ 53 ] obtained, in the same species, values ranging from 35.60 to 49.69 mg/100 g fw.…”
Section: Resultsmentioning
confidence: 99%
“…Organic plant management is represented by systems that are stabilized for years. To better understand the chemical composition of organic and conventional plants, long-term experiments should be conducted [22][23][24][25][26]. In the present literature, only a few experiments were conducted with the distribution of phenolic and carotenoid compounds in plant tissues, but not with basil, especially in comparison between organic and conventional plants.…”
Section: Introductionmentioning
confidence: 99%